Economic and Clinical Impact of Stroke and Warfarin Use for Patients with Non-valvular Atrial Fibrillation - Li Wang; Elyse Fritschel; Onur Baser (Journal of Health Economics and Outcomes Research)
**Background:** Atrial fibrillation (AF) is a common clinical problem and potent risk factor for stroke. However, real-world effectiveness and outcomes for AF patients are not well described.